The effect of peer coaching on teachers’ digital storytelling based teaching practices - Mustafa Emrullah Akbaba; Esma Genç (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The research aims to explore the influence of peer coaching on the lesson planning and implementation processes based on the digital storytelling method. The case-study research involved 12 week peer coaching initiative focused on lesson planning and implementation based on the digital storytelling method with two teachers. In the research, data were collected through interviews, meeting reflection forms, lesson-planning rubrics and lesson observation forms; content analysis was used in the analysis of the data. The overall conclusion drawn from this research suggests that the implementation of peer coaching positively influences the lesson planning and implementation process. Furthermore, the peer coaching process can serve as an effective strategy for facilitating professional development and providing the emotional support that is essential for teachers. Given the research outcomes, it is suggested that more extended periods of peer coaching cycles, reiterated more than once, should be implemented, and the impact of these practices on student learning should be further explored.